فهم الحديث الشريف في ضوء السياق التاريخي والزماني - Ramle, M. R. bin.; Mohamed Maiddin, S. H.; Abdul Hadi, A. Z. S. (Universiti Sains Islam Malaysia, 2024)
The discussion on the principles and rules to understand the text of prophetic traditions can never be dispensed with by a student of Islamic studies. Hence, we can observe that there are scholars who have developed principles and rules to understand the text of prophetic traditions as a discipline. One of the principles used to understand the text of prophetic traditions is the principle of understanding traditions through historical and temporal contextualization. There is no doubt that the principle of historical and temporal contextualization has a significant contribution to ensure a correct understanding of the prophetic traditions. The failure to refer to, and rely on the principle of historical and temporal contextualization would lead to an inaccurate and incomplete understanding of the prophetic traditions such as in situations when there are seemingly contradictions among several narrations. Therefore, this research aims at highlighting the importance of this principle and unveiling its practical application. In the course of completing this research, I have relied on the inductive and analytical approach.